THE PRINCIPLES OF STABLE OPERATION OF HOUSING AND COMMUNAL SERVICE ENTERPRISES - A. N. Ryakhovskaya (Финансы: теория и практика, 2017)
The reasons for insolvency of municipal unitary enterprises providing housing and communal services (HCS MUE) and their implications for the country and other economic agents are investigated; the necessity and feasibility of including HCS enterprises into a special category of debtors in carrying out bankruptcy procedures are substantiated; the prospects of applying the corporate social responsibility to solving HCS problems are analyzed in the framework of the public-private and municipal-private partnership. One of the principal statutory tasks of a municipal government is to enable the financial stability of HCS MUEs that provide socially significant and vitally important services. At present, however, the above problem in the Russian Federation is not handled properly, as evidenced by the increasing physical depreciation of fixed assets and municipal infrastructure of local communities, as well as by the widespread bankruptcy of municipal.HCS enterprises.